Molecular evidence for a single taxon, Anopheles nuneztovari s.l., from two endemic malaria regions in Colombia - Luz Marina Jaramillo; Lina A Gutiérrez; Shirley Luckhart; Jan E Conn; Margarita M Correa (Memorias do Instituto Oswaldo Cruz, 2011)
To elucidate the Anopheles nuneztovari s.l. taxonomic status at a microgeographic level in four malaria endemic localities from Antioquia and Córdoba, Colombia, fragments of the cytochrome oxidase subunit I (COI) and the white gene were used. The COI analysis showed low genetic differentiation with fixation index (F ST) levels between -0.02-0.137 and Nm values between 3-∞, indicating the presence of high gene flow among An. nuneztovari s.l. populations from the four localities. The COI network showed a single most common haplotype, type 1 (n = 55), present in all localities, as the likely ancestral haplotype. Analysis of the white gene showed that An. nuneztovari s.l. populations from both departments grouped with haplotypes 19 and 20, which are part of lineage 3 reported previously. The results of the present study suggest that An. nuneztovari s.l. is a single taxon in the area of the present study.